2011
DOI: 10.19030/iber.v5i2.3462
|View full text |Cite
|
Sign up to set email alerts
|

A Study Of Motivation In Business Start-Ups Among Malay Entrepreneurs

Abstract: The effect of entrepreneurships in developing economies was studied widely in prior researches, since entrepreneurs contribute significantly in economics development. The purpose of this study is to explore and understand Malay entrepreneurs in the eastern region of Peninsular Malaysia; who are the majority ethnic group in the area. The study is concentrated on the motivation factors that influenced their decision to start up new businesses. This study also examined problems faced by those entrepreneurs, both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Information regarding women's motivations to enter this type of work thus remains scarce. Most studies on the motivational factors for women's entrepreneurship in Malaysia have placed main emphasis upon larger size and more formalized business activities (Gadar and Yunus, 2009; Ismail, 1996; Ismail et al , 2006; Salleh and Osman, 2007; Teoh and Chong, 2007). In some cases women's hawking has fallen outside the scope of these studies because women's small scale‐ or micro‐entrepreneurship have not been classified as “true entrepreneurship” (Hanson, 2009).…”
Section: Gender and Entrepreneurship In Malaysiamentioning
confidence: 99%
See 1 more Smart Citation
“…Information regarding women's motivations to enter this type of work thus remains scarce. Most studies on the motivational factors for women's entrepreneurship in Malaysia have placed main emphasis upon larger size and more formalized business activities (Gadar and Yunus, 2009; Ismail, 1996; Ismail et al , 2006; Salleh and Osman, 2007; Teoh and Chong, 2007). In some cases women's hawking has fallen outside the scope of these studies because women's small scale‐ or micro‐entrepreneurship have not been classified as “true entrepreneurship” (Hanson, 2009).…”
Section: Gender and Entrepreneurship In Malaysiamentioning
confidence: 99%
“…In some cases women's hawking has fallen outside the scope of these studies because women's small scale‐ or micro‐entrepreneurship have not been classified as “true entrepreneurship” (Hanson, 2009). Ismail et al (2006, p. 105), for example explain the low rate of women in their study by stating:Even though there were many women small business owners located in the area of studies, not many were pursuing to become successful entrepreneurs. Many of them were conducting business to earn a living for their family and have no plan to expand further.…”
Section: Gender and Entrepreneurship In Malaysiamentioning
confidence: 99%
“…Besides that, through working experiences, the individuals may develop specific skills and may also help individuals gain knowledge about the industry and identify opportunities to create businesses (Olaechea, 2018). Ismail et al (2006) found that the type of experience from the former work does not significantly influence the individuals' decisions to start up their business. However, a more recent study showed that individuals with experience in management have a higher likelihood of new ventures (Xi et al, 2016).…”
Section: Work Experiencesmentioning
confidence: 87%
“…Research on business startup motivation is also carried out, taking into account specific groups of entrepreneurs, e.g., age or gender. According to the results of Ismail et al [32] and Hazudin et al [33], startup business motives vary based on gender. Women are more likely to engage in business to keep work in balance with family needs, so financial security is very important.…”
Section: Literature Reviewmentioning
confidence: 99%